Optimising microfoundations for inflation persistence - Mash, R (University of Oxford, 2004)
Much recent monetary policy literature has searched for structural models suitable for policy analysis that are both based on optimising microfoundations and consistent with the data, especially observed persistence in inflation and output. Few models do well on both criteria. We derive an optimising model of the Phillips curve based on a generalised time dependent pricing rule, calibrate it using microeconomic evidence on price changing behaviour and simulate it with a standard discretionary policy maker. The model predicts inflation and output persistence comparable to that observed without reliance on rule of thumb behaviour or serially correlated shock processes.